1996
DOI: 10.1073/pnas.93.3.1049
|View full text |Cite
|
Sign up to set email alerts
|

Sterol regulation of acetyl coenzyme A carboxylase: a mechanism for coordinate control of cellular lipid.

Abstract: Transcription from the housekeeping promoter for the acetyl coenzyme A carboxylase (ACC) gene, which encodes the rate-controlling enzyme of fatty acid biosynthesis, is shown to be regulated by cellular sterol levels through novel binding sites for the sterol-sensitive sterol regulatory element binding protein (SREBP)-1 transcription factor. The position ofthe SREBP sites relative to those for the ubiquitous auxiliary transcription factor Spl is reminiscent of that previously described for the sterol-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
99
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(103 citation statements)
references
References 15 publications
3
99
1
Order By: Relevance
“…HMG-CoA synthesis is catalysed by HMG-CoA synthase. While the transcription of this enzyme is regulated by SREBP-1a or -2 (Horton et al 1998), it has been reported that cholesterol reduced the mRNA level of HMG-CoA synthase in hepatocytes (Bennett et al 1995;Lopez et al 1996). Therefore, the HMG-CoA content in the cholesterol diet group was about 90 % of that in the no-cholesterol diet group, a difference that was without significance, although the cholesterol diet group had a significantly higher SREBP-1 mRNA level than the no-cholesterol diet group.…”
Section: Discussionmentioning
confidence: 99%
“…HMG-CoA synthesis is catalysed by HMG-CoA synthase. While the transcription of this enzyme is regulated by SREBP-1a or -2 (Horton et al 1998), it has been reported that cholesterol reduced the mRNA level of HMG-CoA synthase in hepatocytes (Bennett et al 1995;Lopez et al 1996). Therefore, the HMG-CoA content in the cholesterol diet group was about 90 % of that in the no-cholesterol diet group, a difference that was without significance, although the cholesterol diet group had a significantly higher SREBP-1 mRNA level than the no-cholesterol diet group.…”
Section: Discussionmentioning
confidence: 99%
“…10,11) SREBP-1 binds to the sterol regulatory element in the ACC PII promoter to enhance the transcription of PIIgenerated ACC mRNA. 12) Since dietary soy protein reduces SREBP-1 protein content in hepatic nuclei, 5) expression of ACC mRNA generated from PII promoter is presumed to be specifically down-regulated by this alteration in SREBP-1.…”
mentioning
confidence: 99%
“…One of the transcription factors that has been shown to regulate the expression of several key genes of fatty acid and triglyceride metabolism is sterol regulatory element-binding protein (SREBP)1 (12). The family of SREBP-responsive genes, first limited to the LDL receptor and genes involved in cholesterol synthesis, has been expanded to include several additional genes that control lipid metabolism, such as fatty acid synthase (FAS) (13), acetyl-CoA carboxylase (14), glycerol-3-phosphate acyltransferase (15), leptin (16), and lipoprotein lipase (LPL) (17), which are important for adipose tissue metabolism. SREBPs have also been implicated in the enlargement of adipocyte energy stores and obesity (13).…”
mentioning
confidence: 99%